2012
DOI: 10.1074/jbc.m112.397240
|View full text |Cite
|
Sign up to set email alerts
|

The Last Piece in the Vitamin B1 Biosynthesis Puzzle

Abstract: Background:The enzyme synthesizing the pyrimidine moiety (HMP-P synthase or THI5p) of vitamin B 1 is poorly characterized. Results:We determined an atomic model of THI5p and have identified its active site using mutagenesis experiments. Conclusion: THI5p forms a dimer and uses PLP as a substrate rather than as a cofactor. Significance: Our study provides seminal information on the enzymatic mechanism of HMP-P synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 38 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…The finding that SNZ2 and/or SNZ3 are important for thiamine, specifically HMP, synthesis supports a connection between SNZ2/3 and the Thi5p family of enzymes. The poorly characterized Thi5p enzymes use PLP as a substrate rather than a co-factor to generate the HMP-P moiety used for thiamine synthesis (Lai et al 2012; Coquille et al 2012). The finding that the lack of a specific SNZ paralog impacts thiamine biosynthesis, out of many metabolic pathways that use PLP as a cofactor, suggests that there are unique requirements for PLP in this pathway, likely involving the Thi5p family of enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that SNZ2 and/or SNZ3 are important for thiamine, specifically HMP, synthesis supports a connection between SNZ2/3 and the Thi5p family of enzymes. The poorly characterized Thi5p enzymes use PLP as a substrate rather than a co-factor to generate the HMP-P moiety used for thiamine synthesis (Lai et al 2012; Coquille et al 2012). The finding that the lack of a specific SNZ paralog impacts thiamine biosynthesis, out of many metabolic pathways that use PLP as a cofactor, suggests that there are unique requirements for PLP in this pathway, likely involving the Thi5p family of enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The process of thiazole heterocycle formation is relatively well understood both chemically and structurally in prokaryotes and eukaryotes (Chatterjee et al, 2006, 2007; Jurgenson et al, 2006; Kriek et al, 2007). The formation of the pyrimidine moiety, 4-ami-no-5-hydroxymethyl-2-methylpyrimidine phosphate (HMP-P), is catalyzed by the THIC enzyme in bacteria and in plants or by the THI5 proteins in yeast (Wightman and Meacock, 2003; Lawhorn et al, 2004; Raschke et al, 2007; Ishida et al 2008; Lai et al, 2012; Coquille et al, 2012). Isotopic labeling and reconstitution studies have shown that THIC uses 5-amino-imidazole ribonucleotide (AIR) as a substrate (Zeidler et al, 2003; Lawhorn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Opening of the Sc MqnA active site can be seen as a combined result of local conformational changes—especially of the 109 to 112 region—and a slight rotation of the two lobes. Interestingly, other VFT enzymes, such as desulfinase DszB ( 26 ), thiaminase I, and thiamin pyrimidine synthase Thi5 ( 27 , 28 ), also show local rearrangements of loops and α-helices at the opening of the active site, with negligible motion of the two lobes toward each other. Taken together, these observations suggest that enzymes exploit the ligand-binding properties of the VFT fold for specific substrate binding and catalysis but restrict conformational changes largely to the immediate proximity of the active site.…”
Section: Resultsmentioning
confidence: 99%